HEPATITIS B IMMUNOGLOBULIN MONO-PROPHYLAXIS AGAINST HEPATITIS B CORE ANTIBODY POSITIVE GRAFTS IN LIVING DONOR LIVER TRANSPLANTATION. - NULL AUTHOR_ID (2006)
Freire, Maristela P; Figueira, Estela RR; Bonazzi, Patricia P; Bachella, Telesforo; Machado, Marcel CC; Abdala, Edson Author Information